The Role Of Computer Graphics In Working With Colors In Design - H. E.Xalilova; U.T.Rixsiboev (Research Parks Publishing LLC, 2021)
This article discusses the role of computer graphics in working with colors in design. Describes models that work with colors in computer graphics. Information is provided on the convenience and capabilities of the models